Preface - Stewart, Ann (feminists@law, 2014)
This preface introduces the chapter 'Legal Constructions of Body Work' and the book in which it was first published, C. Wolkowitz et al. eds, Body/Sex/Work: Intimate, Embodied and Sexualised Labour (Palgrave Macmillan, 2013).